1985
DOI: 10.1016/0014-5793(85)80761-4
|View full text |Cite
|
Sign up to set email alerts
|

Calcium‐activated, phospholipid‐dependent protein kinase activity and protein phosphorylation in HL60 cells induced to differentiate by retinoic acid

Abstract: Treatment of human promyelocytic (HL60) cells with retinoic acid for at least 48 h causes differentiation to more mature myeloid forms. Prior to commitment of cells to the myeloid pathway there is a marked increase in cytosolic calcium‐activated, phospholipid‐dependent protein kinase activity. This increase does not result from an intracellular redistribution of the enzyme. Concomitant with the increased enzyme activity there is enhanced phospholipid‐dependent phosphorylation of proteins of 29, 49, 52, 58, 68,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…This membrane-bound kinase, originally identifled in brain (82) is widely distributed in cells, appears to be the target for the tumor promoting phorbol esters, and is important in the control of signal transduction and tumor differentiation (83). In myeloid precursors, there is a stimulation of PKC enzyme activity and phosphorylation of its various substrates correlating with RA-induced differentiation (81) occurring prior to the commitment of the cells to the myeloid pathway (84). In contrast, embryonal carcinoma cells exhibit an increase in PKC activity that accompanies but does not precede differentiation (85), suggesting that in the latter system, these effects may be a consequence rather than a cause of differentiation.…”
Section: Ra and Protein Kinase Activitymentioning
confidence: 99%
“…This membrane-bound kinase, originally identifled in brain (82) is widely distributed in cells, appears to be the target for the tumor promoting phorbol esters, and is important in the control of signal transduction and tumor differentiation (83). In myeloid precursors, there is a stimulation of PKC enzyme activity and phosphorylation of its various substrates correlating with RA-induced differentiation (81) occurring prior to the commitment of the cells to the myeloid pathway (84). In contrast, embryonal carcinoma cells exhibit an increase in PKC activity that accompanies but does not precede differentiation (85), suggesting that in the latter system, these effects may be a consequence rather than a cause of differentiation.…”
Section: Ra and Protein Kinase Activitymentioning
confidence: 99%
“…Thus, PKC and PKA regulate a variety of developmental and mature neuronal and nonneuronal processes. Additional studies demonstrated differentiation-specific alterations in PKC and PKA activities (Abraham et al, 1991;Durham et al, 1985;Fontana et al, 1984;Kraft and Anderson, 1993;Plet et al, 1985Plet et al, , 1986Plet et al, , 1987Wooten et al, 1992). These data suggest that alterations in PKC and PKA activities are associated with the development of the mature cellular phenotype.…”
Section: Introductionmentioning
confidence: 83%
“…Granulocytic differentiation is a complex multistep process, involving irreversible changes in gene expression, which implies that many differentiation-inducing signal pathways terminate the nucleus. Modifications of protein kinase C activity in the process of retinoic acid-induced differentiation of HL-60 have been described by several authors (Zylber-Katz & Glazer, 1985;Durham et al, 1985;Makowske et al, 1988;Hashimoto et al, 1990;Devalia et al, 1992;Seibenhener & Wooten, 1992;Yat-Ming Yung & Ka-Way Hi, 1993;Yang et al, 1994). However, some discrepancies exist among these studies on the modifications of the PKC catalytic activity induced by ATRA as well as on its relative contribution to differentiation of the various PKC isoforms.…”
Section: Retinoids Induce Terminal Differentiation Of Blast Cells In mentioning
confidence: 97%